Psidium guajava L. (Common Guava) Peel, Pulp and Leaves as Natural Sources of Antioxidants, Antimicrobials and Photoprotective Agents for Development of Sun Protection Cosmeceuticals - Dewage, D.D.D.H.; Samarakoon, S.M.G.K.; Karunaratne, S.H.S.; Rajapakse, C.S.K. (Asian Journal of Chemistry, 2022)
Sunscreens with natural ingredients for skin care become a new trend in cosmetology as it protects skin against photo-aging and dermatologic disorders. Therefore, the goal of this study was to evaluate the antioxidant, antimicrobial and photoprotective properties of methanolic extracts of leaves, peel and pulp of Psidium guajava L. to investigate their potentials to be used as sources of cosmeceutical ingredients for sun protection. Chemical constituents of the plant parts were extracted into methanol by maceration. Among the extracts, leaf extract exhibited higher DPPH free radical scavenging activity (IC50 = 89.56 ± 0.97 μg/mL), than that of peel and pulp extracts. The highest total phenolic content (TPC) and total flavonoid content (TFC) were found to be in the leaf extract. All extracts demonstrated antibacterial activity against the examined potential pathogens in cosmetic products. Among the extracts, leaf extract showed the highest photoprotective property with the sun protection factor (SPF) of 30.38 ± 0.22 at 2 mg/mL indicating its potential to be used in the development of sunscreen formulations.